The Strategic Role of Islamic Religious Education in Shaping the Values and Character of Adolescents in Lombok (PT. LARPA JAYA PUBLISHER, 2024)
Adolescents face various social and clinical issues, including risky sexual behavior, unwanted pregnancies, sexually transmitted infections (STIs), HIV/AIDS, substance abuse, and other maladaptive behaviors. These problems often arise due to a lack of understanding of Islamic teachings. This study aimed to examine the relationship between Islamic knowledge and adolescent character in Lombok. A descriptive-analytic study with a cross-sectional design was conducted involving 50 adolescents selected through random sampling. Data on Islamic knowledge (independent variable) and adolescent character (dependent variable) were collected and categorized as good, fair, or poor. Data analysis included univariate descriptions of sociodemographic characteristics and bivariate analysis using the Chi-square test with a significance level of p < 0.05. The results indicated a significant relationship between Islamic knowledge and adolescent character (p = 0.000). Adolescents with good Islamic knowledge predominantly exhibited positive character traits, while those with poor knowledge were more likely to display negative behaviors. The findings highlight the importance of Islamic education in shaping moral values, ethical behavior, and social responsibility among adolescents. Integrating Islamic education within family, school, and community settings can strengthen character development, provide moral guidance, and equip adolescents to navigate modern societal challenges, including technology and social media exposure. This study underscores the critical role of Islamic education as both a source of religious knowledge and a foundation for fostering responsible, ethical, and socially competent adolescents.